Embodied cognition and emotional disorders: Embodiment and abstraction in understanding depression. Issue 3 (19th July 2018) - Gjelsvik, Bergljot; Lovric, Darko; Williams, J. Mark G.
Research into embodied cognition (EC) in cognitive neuroscience and psychology has risen exponentially over the last 25 years, covering a vast area of research; from understanding how ability to judge speech sounds depends on an intact motor cortex, to why people perceive hills as steeper when carrying a heavy backpack. Although there are many theories addressing these phenomena, increasing evidence across EC studies suggests simulation (i.e., re-enactment of the motor-sensory aspects of meaning) as an important basis of knowledge. The authors 1) review evidence for the EC paradigm's claim to simulation effects in cognition, suggesting that simulation exists within a "distributed plus hub" model, 2) discuss the implications of simulation for the understanding of cognitive dysfunctions in emotional disorders, particularly depression, 3) suggest that emotional disorders arises as a result of failed simulation processes, hypothesizing that semantic processing reactivates motor-sensory simulations previously associated with low mood ( enactment/re-enactment networks ), and that truncation of such simulation by means of over-use of language-based, abstract processing, motivated by a wish to reduce the affective disturbance associated with episodic, embodied representations, maintains psychopathology, 4) review evidence for effects of truncated simulation on emotional pathology, and 5) discuss the relevance of EC to treatments of emotional pathology.